Decarbonising the lime industry: State-of-the-art. (October 2022) - Simoni, Marco; Wilkes, Mathew D.; Brown, Solomon; Provis, John L.; Kinoshita, Hajime; Hanein, Theodore
Abstract: The thermal treatment of limestone (mainly CaCO3 ) to produce lime (CaO) is a major contributor to CO2 emissions and the literature on decarbonising the lime industry is scarce. Subsequent hydration of lime would lead to the synthesis of slaked/hydrated lime Ca(OH)2 ; the production of a tonne of Ca(OH)2 emits ∼1.2 tonnes of CO2 arising mainly from the process chemistry and fossil fuel combustion. Carbon Capture & Storage (CCS) technologies are currently believed to have the highest potential to mitigate these CO2 emissions, assuming that the thermal calcination of CaCO3 is unavoidable. Despite intensive research efforts and development, CCS technologies cannot be industrially applied yet due to their limited efficiency and the associated capital and operational costs. In this review, the current state of the lime industry and its processing configurations is visualised. This is followed by a detailed description of the current status of the relevant CCS technologies (including their CO2 avoidance costs) and eco-efficient alternative fuels. This work then gives voice to two novel and potentially more sustainable decarbonisation routes that do not involve the thermal calcination of CaCO3, one of which involves simultaneous mineralisation leading to permanent storage of CO2 . These technologies are particularly interesting especially if high temperature lime kilns, as we know them, are phased out to meet climate goals. It is revealed that the energy shift to green electricity might lead to a no-carbon lime industry and subsequent carbon neutrality (or negativity) of other hard-to-abate sectors. Highlights: Descriptions of the lime (and slaked lime) production processes and configurations . Overview of carbon capture technologies available for the lime industry. Discussion of alternative fuels avalaible for low-carbon lime production. Highlights of the routes availablefor non-thermal decarbonisation of CaCO3 .